Fe-doped boron nitride for adsorption of oxytetracycline in pharmaceutical wastewater - WANG Yong; WU Haofeng; JIN Yan; LUO Guiling; CHAO Yanhong; ZHU Wenshuai* (能源环境保护)
To reduce the environmental pollution of oxytetracycline (OTC) in pharmaceutical wastewater, Fe-doped boron nitride nanosheets (Fe-BN) were synthesized in one step with a green and rapid ball milling process, and the adsorption performance of oxytetracycline on them was investigated. The shear stress provided by the mill balls completed thinning and Fe doping of BN at the same time. The properties of the adsorbent were analyzed by XRD, FTIR, XPS, TEM and nitrogen adsorption. Fe(5%)-BN with the best performance was selected for comprehensive adsorption performance and mechanism research, and the results showed that the specific surface area of it was enhanced more than 3 times after 45 minutes of ball milling. Fe element was mainly doped in the BN lamellar structure in the form of Fe_2O_3. Compared with commercial boron nitride, the adsorption capacity of OTC on Fe(5%)-BN increased by 7.7 times. The adsorption conforms to the quasi-second-order kinetic model and Freundlich isotherm model and the adsorption process is spontaneous endothermic. The adsorption is mainly through cation bridge, electrostatic interaction and π—π interaction. After four adsorption-desorption cycles, the removal efficiency of OTC was still higher than 94%, indicating the good cyclic stability of Fe(5%)-BN.